Funding Public Transportation Through Special Assessment Districts: Addressing the Equity Concerns. (April 2015) - Mathur, Shishir
Little scholarly attention has been paid to the equity impacts of special assessment districts (SADs) established to fund public transportation projects. This article uses three recent public transportation projects funded using SADs in the United States and finds that the case study SADs' performance is mixed. Although the districts use a variety of criteria, such as property value, parcel area, and distance from the transportation project, to calculate assessments in a way that promotes horizontal equity, the assessment methodologies do not take into account the disamenity associated with certain elements of public transportation projects, such as the rail line. Furthermore, owner-occupied residential properties are often exempt from paying assessments to garner support for SADs, rather than to satisfy equity concerns. Finally, the low-interest, long-term payment of assessments enhances vertical equity which can be further enhanced if assessment exemptions or deferments are consistently provided to seniors on fixed incomes and low-income households.